Adoption of Sarbanes‐Oxley Act in China: Antecedents and Consequences of Separate Auditing. Issue 2 (17th December 2015) - Zhang, Jidong; Han, Jing
Abstract : This study examined Chinese public companies' reactions to regulations imposed by the Enterprise Internal Control Standard (the Chinese version of the Sarbanes‐Oxley Act). We found some Chinese public companies used separate CPA firms to audit their internal control over financial reporting and financial statements – a practice that has not been addressed in prior studies on SOX adoption. In this paper, we examine the antecedents and consequences of separate auditing. First, because audit quality is an important aim of the Enterprise Internal Control Standard, we tested the influence of separate auditing on audit quality. Moreover, we theorized and hypothesized that a company's decision to employ separate auditing was influenced by the presence and proportion of directors on the board who performed multiple functions, thus affecting their concerns about the company's internal and external relations. An empirical analysis of 113 public Chinese companies that voluntarily disclosed and audited their internal control reports confirmed our hypotheses. Contribution to the literature, practical implications, and limitations are also discussed.